Determination of Aflatoxin Levels in Cereals and Leguminous Grains Selected Cereals and Leguminous Grains Retailed in Wukari, Taraba State - Chinonso, Anih David; Kayode, Arowora; Umaru, Isaac John; Chinedu, Imo; Ale, Ebenezer Morayo; Oladele, Gloria Omonefe (African Journal of Sciences and Traditional Medicine, 2024)
Aflatoxins are group of secondary fungal metabolites produced by Aspergillus species, such as Aspergillus flavus and Aspergillus parasiticus. The aflatoxin producing moulds can grow on cereals and legumes in the field, poorly dried harvested crops in storage, processed food, and feed products. The study was carried out with the aim to determine the level of aflatoxin contamination of cereals grain and legumes retailed in Wukari, Taraba State Nigeria. A total Sixty-three (63) samples were procured from different vendors from the markets namely, new and old markets in Wukari and Dorowa Market, which comprises of 3 samples each of millet, maize, rice, groundnut, sesame seeds and soy beans. The samples were grounded and extracted with 80% (v/v) methanol. The enzyme-linked Immunosorbent Assay (ELISA) technique was used in quantifying the total aflatoxin content of the samples. The results revealed that there were no significant differences in the aflatoxin levels of shelled melon seeds while there was a significant difference in shelled groundnut, soybeans and millet samples purchased from all the markets. Aflatoxin levels in cereals and legumes retailed in Wukari, Taraba State ranged from 0.57-1.17µg/kg in shelled groundnut samples, 0.47-2.27µg/kg in shelled melon samples, 1.53-3.17µg/kg in sesame seed samples, 0.10-0.20µg/kg in soybean samples, 3.11-13.10µg/kg in maize samples, 6.13-15.4µg/kg in millet samples, and 0.471.0µg/kg in parboiled rice samples. the levels of aflatoxin in the samples which was observed to be highest in millet sample procured from Dorowa market with a value of 15.43±0.15% and lowest in soy bean bean sample procured from Dorowa and New market Wukari with a value of 0.10±0.00%. These aflatoxin levels were within the permissible limits for total aflatoxins recommended by FDA and NAFDAC for all products intended for food, hence these cereals and legumes analysed in this study are safe for human consumption.